Mobile robotic systems with walking movers and mechanisms of orientation - Korendiy, Vitaliy; Bushko, Oleksandr; Denderys, Nazar (Lviv Polytechnic Publishing House, 2015)
The expediency and areas of use of walking machines are substantiated. Three simplest diagrams of cyclic (lever) walking mechanisms (four-link, four-link with possibility of changing the position of the rocker arm rotation axis, six-link) are considered. Principal diagram of the lever mechanism of orientation of walking module with two cyclic movers is propounded and its operating features are analyzed.
Keywords: mobile robotic system; walking mover; mechanism of orientation; principal diagram; operation features; motion parameters; mechanical trajectory of the pivot foot